Sustainable performance measurement (SPMs) model: effects of product technology and process technology - Boon, Heng Teh; Tze, San Ong; Jaffar, Nahariah; Masoudi, Sayed Yousef Sheikh Abou (Universiti Putra Malaysia Press, 2015)
Malaysia as a developing country is in the transformation process of becoming an industrialised nation, as stated in Vision 2020. Manufacturing industry significantly contributes to the national economic growth in Malaysia; however, the manufacturing industry consumes the most natural resources which cause degradation of natural resources. This is against the global efforts that put pressure on world organisations to carry out their business in a more responsible and sustainable manner. As an approach to improve sustainability performance, manufacturing companies should develop technologies that consume less material, while trying to adopt new technologies effectively. However, empirical studies in Malaysian manufacturing industry on technology and Sustainable Performance Measurements (SPMs) are still very limited. Thus, the main purpose of this study is to determine the relationship between technology and Sustainable Performance Measurements (SPMs) model among different sizes of Malaysian manufacturing companies. The target population in this research is 2500 manufacturing companies registered under Federation of Malaysian Manufacturers (FMM). The random sampling method is engaged in the sample selection. A total of 217 observations were collected over 600 sample size, with a response rate of 36.17%. The results of the analysis indicate that product technology does not have any significant effect on SPMs. In contrast,process technology demonstrates a positive relationship with SPMs. In addition, business size does not affect SPMs. Overall, it can be concluded that Malaysian manufacturing companies consider more privilege for process technology implementation to achieve desirable SPMs performance in their business rather than product technology.